Enhancing service requirements of technical product-service systems - Estebanez, L. Ruiz; Shehab, Essam; Sydor, Piotr; Mackley, Tim; John, Philip; Harrison, Andrew (Elsevier, 2015)
Due to the integration of product and services as a new business model, product reliability and strategies for cost reduction at the early design stage have become important factors for many manufacturing firms. It is, therefore, critical at this phase to analyse the risk involved with Service Requirements noncompliance in order to help designers make informed decisions; as these decisions have a large impact on the Product Life Cycle (PLC). An investigation has been performed into how Service Requirements are analysed in a service orientated business to achieve reduced Life Cycle Cost (LCC) and improvements of existing Service Requirements. Weibull distribution and Monte Carlo principle have been proposed to do so; as they are considered as the most widely used in product reliability studies in the industry sector. A generic methodology for risk evaluation of failure to deliver a new product against Service Requirements is presented in this paper. This is part of the ongoing research project which aims to, apart from comparing current and targeted Service Requirements, it also facilitates an optimisation of them at the minimum risk of nonconformity.
Keywords: PSS; Service Requirements; Weibull Distributions; Risk; Decision-Making